2020
DOI: 10.3390/polym12061335
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Self-Lubricating Porous UHMWPE with Excellent Mechanical Properties and Friction Performance via Rotary Sintering

Abstract: Porous ultra-high-molecular-weight polyethylene (UHMWPE) self-lubricating materials were designed and fabricated by a rotary sintering method, and the microstructure and properties were evaluated. Results showed that the rotary molding could not only significantly improve the molding efficiency but also formed uniform internal microstructures with high porosity, excellent mechanical properties, and low friction coefficient. Under oil lubricating conditions, the friction curve of samples quickly reached a stead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…(a) Rotary sintering plant, 34 (b) preparation process of porous matrix and CPCM [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Rotary sintering plant, 34 (b) preparation process of porous matrix and CPCM [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Methodsmentioning
confidence: 99%
“…33 UHMWPE with 3D porous structure can be formed by controlling the sintering process. Additionally, UHMWPE and PW have the similar chemical structure and good compatibility, 34 which is beneficial to the adsorption of PW by UHMWPE. Nevertheless, to our best knowledge, the use of rotary sintered UHMWPE as the porous carrier of CPCM has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…PTFE, UHMWPE, Molybdenum disulfide (MoS 2 ), SiC, carbon fiber, etc. Are used as lubricant materials or reinforcing fillers to improve the friction properties of polymers (Li et al, 2007;Chanda et al, 2019;Salem et al, 2019;Cao et al, 2020). Among them, CNTs are the ideal modifiers for the fabrication of polymer composites with high tribological properties due to their unique structures and excellent properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although the rise in temperature causes the degradation and decomposition of UHMWPE, and therefore, the mechanical and tribological properties (Golmakani et al , 2021). Cao (2020) used sintering to fabricate porous self-lubricating materials from UHMWPE. The test results showed that the specimens with a sintering temperature of 180°C or 190°C, sintering time of 10 min kept low friction coefficients and wear rates.…”
Section: Introductionmentioning
confidence: 99%